Cyclic Voltammetry and Oxidation Rate Studies of Ferrous Gluconate Complex Solutions for Preparation of Chitosan-Tripolyphosphate Microparticles - Noer Abyor Handayani; Elsa Anisa Krisanti; Sutrasno Kartohardjono; Kamarza Mulia (Journal of Chemistry)
A proper understanding of the properties of iron could increase the effectiveness of programmes for alleviating iron deficiency. Recently, encapsulation has been considered an appropriate method for protecting iron from injurious reactions. However, several events may occur during encapsulation processes, including changes in the iron’s oxidation state. Oxidation of ferrous iron is not desirable since the intestines can only absorb iron in the ferrous form. In this study, a cyclic voltammetry method was applied to investigate the likelihood of ferrous gluconate oxidation for the preparation of chitosan-tripolyphosphate microparticles. Then, the electrochemical properties of ferrous gluconate were confirmed experimentally. The oxidation rate of ferrous gluconate is also discussed in this paper. All the experimental solutions were formulated in detail to produce conditions similar to those of microparticle production. Cyclic voltammetry analysis was conducted using a configuration of three electrodes connected to an electrochemical analyser. Graphite, platinum wire, and Ag/AgCl were employed as the auxiliary, working, and reference electrodes, respectively. The cyclic voltammetry results show that the observed potential for each anodic peak shifted negatively in the presence of chitosan and sodium tripolyphosphate. Moreover, the rate of ferrous oxidation tended to increase during 75 min of experiments due to the presence of chitosan and sodium tripolyphosphate. These behaviours indicate the transformation of ferrous iron to ferric iron during iron microparticle preparation. Furthermore, these findings suggest that spray drying is a preferable method to minimise the oxidation reaction.